MiR-183-5p regulates uterine receptivity and enhances embryo implantation. (January 2020) - Akbar, Rubab; Ullah, Kamran; Rahman, Tanzil Ur; Cheng, Yi; Pang, Hai-Yan; Jin, Lu-Yang; Wang, Qi-Jing; Huang, He-Feng; Sheng, Jian-Zhong
Abstract : Receptive endometrium is a prerequisite for successful embryo implantation, and it follows that poor endometrial receptivity is a leading cause of implantation failure. miRNAs play important roles as epigenetic regulators of endometrial receptivity and embryo implantation through post-transcriptional modifications. However, the mechanisms of action of many miRNAs are poorly understood. In this study, we investigated the role of the miR-183 family, comprising three miRNAs (miR-183-5p, miR-182-5p, and miR-96-5p) in endometrial receptivity and embryo implantation. The miR-183 family shows estrogen-dependent upregulation in endometrial Ishikawa (IK) cells. The miR-183 family also has a positive role in migration and proliferation of IK cells. Furthermore, JAr spheroid attachment experiments show that attachment rates were significantly decreased after treatment of IK cells with inhibitors for miR-183-5p and miR-182-5p and increased after treatment with miR-183-5p-mimic and miR-96-5p-mimic, respectively. The downstream analysis shows that catenin alpha 2 ( CTNNA2 ) is a potential target gene for miR-183-5p, and this was confirmed in luciferase reporter assays. An in vivo mouse pregnancy model shows that inhibition of miR-183-5p significantly decreases embryo implantation rates and increases CTNNA2 expression. Downregulation of CTNNA2 in endometrial cells by miR-183-5p may be significant in mediating estrogenic effects on endometrial receptivity. In conclusion, miR-183-5p and the CTNNA2 gene may be potential biomarkers for endometrial receptivity and may be useful diagnostic and therapeutic targets for successful embryo implantation.